2015
DOI: 10.4315/0362-028x.jfp-15-102
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Hand Hygiene Interventions Using Alcohol-Based Hand Sanitizers and Soap To Reduce Microbial Load on Farmworker Hands Soiled during Harvest

Abstract: Effective hand hygiene is essential to prevent the spread of pathogens on produce farms and reduce foodborne illness. The U.S. Food and Drug Administration Food Safety Modernization Act Proposed Rule for Produce Safety recommends the use of soap and running water for hand hygiene of produce handlers. The use of alcohol-based hand sanitizer (ABHS) may be an effective alternative hygiene intervention where access to water is limited. There are no published data on the efficacy of either soap or ABHS-based interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…These two observations together suggest that hands are a reservoir of microorganisms and an important vehicle for their transfer to fresh produce during manual production, harvesting, and/or packing (32-34), common practices in produce production in this region (32). Though no other studies to date that we know of have quantified the relationships of microbes between hands and produce in the agricultural environment, this implication is consistent with those of other studies suggesting that hands are an important vehicle of contamination of produce (13,(33)(34)(35)(36). We hypothesize that microorganisms measured in our study could have been transferred either from hands to produce or produce to hands, as has been demonstrated to occur (33,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These two observations together suggest that hands are a reservoir of microorganisms and an important vehicle for their transfer to fresh produce during manual production, harvesting, and/or packing (32-34), common practices in produce production in this region (32). Though no other studies to date that we know of have quantified the relationships of microbes between hands and produce in the agricultural environment, this implication is consistent with those of other studies suggesting that hands are an important vehicle of contamination of produce (13,(33)(34)(35)(36). We hypothesize that microorganisms measured in our study could have been transferred either from hands to produce or produce to hands, as has been demonstrated to occur (33,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 80%
“…We hypothesize that microorganisms measured in our study could have been transferred either from hands to produce or produce to hands, as has been demonstrated to occur (33,(37)(38)(39). These findings and our hypothesis led to testing the effectiveness of hand hygiene interventions (soap, hand sanitizer) to improve the microbial quality of hands and produce (33,34). These intervention trials on farms showed that farm worker hands treated with hand hygiene products had significantly lower microbial levels immediately following hand hygiene treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand sanitizer has been shown to be effective in reducing bacterial counts by up to 90% when used correctly in healthcare settings and still reduces bacterial counts significantly with less optimal use by >50% (11). While the effectiveness of hand sanitizer has not been specifically studied in therapy animal situations, it has been shown to be as effective as handwashing in agricultural settings such as livestock shows, petting zoos, and farm employees in reducing bacteria loads, particularly of enteric pathogens such as Escherichia coli and Salmonella (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Although handwashing is widely considered to be an important part of disease prevention and studies show that it is effective for preventing transmission of infection [ 20 23 ], studies on handwashing efficacy for the removal or inactivation of a range of organisms from hands using different protocols have shown inconsistent results. In an informal literature search, we identified 14 studies that compared the efficacy of HWWS and ABHS on the removal of organisms: of these, seven found HWWS to be more efficacious [ 24 – 30 ], five found ABHS to be more efficacious [ 31 35 ], and two found little difference between the methods [ 36 , 37 ]. One of these manuscripts showed that while some soaps were more efficacious than ABHS, others were not.…”
Section: Introductionmentioning
confidence: 99%